Medical Students' Perception of Community-Based Education Research and Services (COBERS) In Mbarara University of Science and Technology. - Naali, Ritah (Student's Journal of Health Research Africa, 2021)
Background: The success of the Community Based Education Research and services (COBERS) in Mbarara University of Science and Technology plays a fundamental role in improving the community's health, education, and economics by sharing knowledge obtained from projects and increases the student's interest and participation in research while fulfilling the mission and vision of the university. The Student's perception of the Program contributes to compliance by Students to work in rural areas upon graduation, increases trust from communities, enhances the behavioral change and decreases costs to health departments, and facilitates development and implementation of more effective public health interventions. Most published studies reporting students' perceptions of COBERS are mainly from the developed world and only a few in Africa including Uganda. This report explored the overall Students Perceptions of COBERS at Mbarara University of Science and Technology. Methodology: A qualitative descriptive design was employed. The study involved thirty-three Medical students who were selected by purposive sampling. Data was collected using focused group discussions and analyzed manually to generate themes and subthemes. Results: Four themes emerged from eighteen categories describing Medical Students Perception of COBERS: An opportunity for interactions, the program is challenging, Attainment of skills, and an opportunity for interactions. These Qualitative findings reveal mixed feelings about COBERS. Conclusion: In conclusion, the four themes; An opportunity for interactions, the program is challenging, attainment of skills, an opportunity for translating theory to practice that emerged from eighteen categories were mostly expressions of perceptions of COBERS. These qualitative findings suggest that students' acceptance of COBERS as a requirement for Medical Schools is based on their perception of the expected outcome and the perceived benefits of their contribution to the community. These findings were from five focused group discussions where participants participated voluntarily in the study.